Assessing the competitiveness of Matera and the Basilicata Region (Italy) ahead of the 2019 European Capital of Culture. (October 2019) - Aquilino, Lucia; Armenski, Tanja; Wise, Nicholas
Cities/regions are increasingly using events to aid social/economic development. The European Capital of Culture promotes urban management and economic production using culture to drive social legacies, job creation and civic repositioning. This paper aims to understand how Matera and Basilicata's residents perceive destination competitiveness ahead of the 2019 European Capital of Culture. This paper adapts the Integrated Model of Destination Competitiveness and suggests a new determinant to understand resident perceptions. This paper contributes a new determinant to consider in competitiveness research: social conditions to improve local wellbeing. Two hundred respondents identify strengths/weaknesses of each competitiveness determinant. The results presented in this study display sample mean values and standard deviations for each indicator, as well as Wilcoxon test statistic (z). Competitive indicators are those showing means above 4.0. Descriptive and inferential analyses using SPSS 17 show strengths/weaknesses comparing Matera (city) and Basilicata (region) with similarities and differences outlined to consider both urban and regional perspectives and differences. For the data analysis, Wilcoxon paired signed rank test displays differences in the competitiveness factors between Matera and Basilicata. Wilcoxon (a nonparametric alternative to paired sample t-test) was performed since the data distribution was left skewed and Kolmogorov–Smirnov statistic indicates violation of normality assumption. Results show the majority of inherited, created and supporting resources are competitive, as well as image and social conditions; however, management and organisation needs improvement. It is essential that European Capital of Culture hosts have long-term competitive strategies in place to strengthen urban and regional capacity when delivering diverse cultural programmes, at present, and into the future. This study offers insight before the 2019 European Capital of Culture to inform planners and policymakers ahead of the event and offers consideration and discussion of social impacts and the need to gain such insight in competitiveness research going forward.